(untitled) (Journal of the College of Basic Education, 2022)
The theater cannot assert its influential aesthetic and cognitive presence without the cohesion of a group of audiovisual and kinetic components in establishing its spectacle systems at the level of organization, discipline and accuracy. Presence.And in our focus on the kinetic component and its importance in making theatrical show because it is the most obvious and influential aspect in its conformity with the reality that the text weaves in front of us, as well as the ability of the kinetic component to draw images of scenes and the interaction of other components with it on the basis that the movement that emerges and is built in the show, whether it is an actor, light or decor All tags are produced inside the view structure.